The association between hot days and substance-related suicides: a time-stratified case-crossover analysis in British Columbia, Canada - Karen Li; Sarah B. Henderson; Eric S. Coker; Kathleen E. McLean; Michael Joseph Lee (Environmental Health)
Abstract Background Hot weather can negatively impact mental health and increase the risk of suicide. The relationship between heat and risk of suicide is not fully understood, and varies geographically across regions with differing climates, cultures, and socio-economic factors. The objective of this study was to investigate the relationship between hot summer days and suicides in British Columbia, Canada (BC). Methods A time-stratified case-crossover design was used to estimate the relationship between hot days (exposure) and suicide (outcome), considering same-day and two-day mean temperature. Conditional logistic regression was used to estimate the odds ratio (OR) for the association between hot days and suicides for three outcomes including: (1) suicide attempts by self-poisoning extracted from BC Drug and Poison Information Centre (DPIC) database (2012–2023); (2) completed suicides by self-poisoning extracted from BC vital statistics (2004–2023); and (3) completed suicides by violent methods extracted from BC vital statistics (2004–2023). Analyses were stratified by sex, age, ecological region, substance types used in self-poisonings, and by methods of violent suicide. Results There were 9,599 suicide attempts via self-poisoning and 2,571 suicide deaths included in this study. Overall, hot days were associated with increased odds of self-poisoning suicide attempts and deaths, but not with suicide deaths via violent methods. The odds ratio [95% confidence interval] for suicide attempts via self-poisoning on hot days was 1.19 [1.11, 1.29], and 1.48 [1.12, 1.95] for suicide deaths. There was no effect of hot days on suicide deaths by violent methods. The associations varied by day of exposure, sex, age groups, and geography. The effect of hot days was greatest for suicide attempts and deaths involving opioids and elevated for suicide attempts involving opioid and analgesia combinations, analgesics alone, and alcohol. Conclusions The risk of suicide via self-poisoning was increased on hot summer days in BC, Canada. However, the relationship was influenced by other factors that vary among individuals and geographies. Policy decisions and future research for suicide-prevention during hot weather should consider sub-population susceptibility.